Draft Annual Plan 1988-89 Vol-IV - Planning Commission (Planning Commission, 1988)
The objective and strategy of the Seventh Five Year Plan are in a nut-shell as follows To provide universal schooling facilities, To provide primary schooling facilities closer to the home of the children. To ensure 100% enrolment of all children of 6-11 age-group. To shift the emphasis from-more enrolment to retention of children after enrolment particularly in elementary stage. To improve the physical facilities in schools. To try out the ideas of non-formal education at the elementary stages.
Government of Tripura